Percepción de los efectos económicos-financieros-sociales de los incentivos tributarios: en la contratación de personal con discapacidad y la deducción para el cálculo del impuesto a la renta de la compensación adicional para el pago del salario digno, en el sector de seguridad privada en el periodo 2012-2013 en el Distrito Metropolitano de Quito. - Endara Caisaguano, Nataly Evelin (2014)
Tax incentives are a way that the Government uses for helping enterprises to submit taxes in exchange for social, environmental and financial support as well as job opportunities and investment. The Internal Revenue Service offers benefits and bonuses supported by the Organic legislation of Internal Taxing Regimen (LORTI) and Organic Code of Production, Commerce and Investment (COPCI) through tax administration where bonuses for hiring disabled people are found or paying a decent wage that are deducted from the Income Tax. Security enterprises have the obligation to hire disabled workers and pay a decent salary to their employees according to Ecuadorian laws.